FISHing with immunohistochemistry for housekeeping gene changes in Alzheimer's disease using an automated quantitative analysis workflow. Issue 4 (2nd February 2021) - Highet, Blake; Vikas Anekal, Praju; Ryan, Brigid; Murray, Helen; Coppieters, Natacha; Victor Dieriks, Birger; Singh‐Bains, Malvindar K.; Mehrabi, Nasim F.; Faull, Richard L. M.; Dragunow, Michael; Curtis, Maurice A.
Abstract: In situ hybridization (ISH) is a powerful tool that can be used to localize mRNA expression in tissue samples. Combining ISH with immunohistochemistry (IHC) to determine cell type provides cellular context of mRNA expression, which cannot be achieved with gene microarray or polymerase chain reaction. To study mRNA and protein expression on the same section we investigated the use of RNAscope® ISH in combination with fluorescent IHC on paraffin‐embedded human brain tissue. We first developed a high‐throughput, automated image analysis workflow for quantifying RNA puncta across the total cell population and within neurons identified by NeuN + immunoreactivity. We then applied this automated analysis to tissue microarray (TMA) sections of middle temporal gyrus tissue (MTG) from neurologically normal and Alzheimer's Disease (AD) cases to determine the suitability of three commonly used housekeeping genes: ubiquitin C ( UBC ), peptidyl‐prolyl cis‐trans isomerase B ( PPIB ) and DNA‐directed RNA polymerase II subunit RPB1 ( POLR2A ). Overall, we saw a significant decrease in total and neuronal UBC expression in AD cases compared to normal cases. Total expression results were validated with RT‐qPCR using fresh frozen tissue from 5 normal and 5 AD cases. We conclude that this technique combined with our novel automated analysis pipeline provides a suitable platform to study changes in gene expression in diseased human brain tissue with cellular and anatomical context. Furthermore, our results suggest that UBC is not a suitable housekeeping gene in the study of post‐mortem AD brain tissue. Abstract : We developed a high‐throughput, automated image analysis workflow for quantifying RNA puncta. We then applied this custom automated analysis method to sections of middle temporal gyrus tissue (MTG) from neurologically normal and Alzheimer's Disease (AD) cases to determine the suitability of three commonly used housekeeping genes: ubiquitin C (UBC), peptidyl‐prolyl cis‐trans isomerase B (PPIB) and DNA‐directed RNA polymerase II subunit RPB1 (POLR2A). We believe that this technique when combined with our novel custom automated analysis pipeline provides a suitable platform to study changes in gene expression in diseased human brain tissue with cellular and anatomical context.